2016
DOI: 10.1515/sagmb-2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Using persistent homology and dynamical distances to analyze protein binding

Abstract: Persistent homology captures the evolution of topological features of a model as a parameter changes. The most commonly used summary statistics of persistent homology are the barcode and the persistence diagram. Another summary statistic, the persistence landscape, was recently introduced by Bubenik. It is a functional summary, so it is easy to calculate sample means and variances, and it is straightforward to construct various test statistics. Implementing a permutation test we detect conformational changes b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 44 publications
0
103
0
Order By: Relevance
“…Related work. Persistence landscapes have been used to study the geometry of microstructures [12]; protein conformations [24]; and financial times series [17]. Average persistence landscapes and average death vectors were used to detect differences in images of leaves in [29].…”
Section: 2mentioning
confidence: 99%
“…Related work. Persistence landscapes have been used to study the geometry of microstructures [12]; protein conformations [24]; and financial times series [17]. Average persistence landscapes and average death vectors were used to detect differences in images of leaves in [29].…”
Section: 2mentioning
confidence: 99%
“…Ours is not the first application of topology to medicinal chemistry: One of the early applications of persistent homology was to protein docking [3], which continues to be an area of active exploration [69,70,44], though the details of the approach taken in those work are rather different than ours. More recently, there have been results in structure-based screening using standard (single-parameter) persistent homology together with machine learning [14].…”
Section: Related Workmentioning
confidence: 96%
“…They achieved a classification accuracy of 69.86 percent. Kovacev-Nikolic et al (2016) used TDA to study the maltose binding protein which is a protein found in Escherichia coli. An example of such a protein is given in Figure 24; the figure is from http://lilith.nec.aps.anl.gov/ Structures/Publications.htm.…”
Section: Imagesmentioning
confidence: 99%